On some syntactic phenomes in Topol's prose Citlivy clovek - Schneiderova, Sona (Bohemica Olomucensia, 2019)
The study deals with the syntactic structure in Topol's prose Citlivy clovek. The author of the study chooses a repetitive syntactic scheme and typical structures of sentence. It shows that Topol works with asyndetone, polysyndetone, juxtaposition, various types of attributes, circumstance determination and graphic signals such as colon. The author of the study focuses on the means of prose rhythmization and contradictory processes in Topol's text - spoken and expanded structures on the contrary condensation of expression.
Keywords: Jachym Topol; prose; asyndetone; polysyndetone; juxtaposition; attribute; circumstance determination; word order; rhythmization; condensation of expression; spoken